Human perception towards fire safety awareness in Malaysia public hospital. - Senin, Zamri (Global Academic Excellence (M) Sdn. Bhd. (GAE), 2023)
The focus of this research is on human perception toward fire safety awareness in public hospitals. The perception was evaluated by looking at two variables, awareness, and knowledge. With the existence of knowledge and awareness, the perception of fire safety in hospitals is high. Thus, the three objectives are; i) evaluate and identify the relation of consumer perception towards the fire safety awareness in hospitals. ii) evaluate and analyse consumer perception on fire safety awareness with the effective value of designs and exit routes prepared. iii) suggest improvement measures in ensuring the hospital’s occupants able to increase the awareness and understanding values in fire safety in hospitals. This study adapted quantitative methodology by using a random survey as an instrument which involved 285 respondents representing 6 selected hospitals in Malaysia. The findings found that there was no significant between the relation of awareness and knowledge with age, education, and occupation in identifying the level of awareness and knowledge in fire safety in hospitals. Yet, there was a significant value in gender which the men have higher awareness and knowledge as compared to women who were not significant in this study. Therefore, several improvement measures need to be done by the hospital administration to add awareness value among the hospital users.